18. The Effect of Sipatah-Patah (Cissus quadrangularis Salisb) Extract on Mandible Density of Ovariectomized Rats (Rattus norvegicus) - Indah Maghfirah; Muhammad Jalaluddin; Dian Masyitha; Mustafa Sabri; Fadli A Gani; Herrialfian Herrialfian (Jurnal Medika Veterinaria, 2018)
The aim of this research was to identify the effect of sipatah-patah (Cissus quadrangularis Salisb) leaf extract on mandible density of ovariectomized rats (Rattus norvegicus). The samples were 12 female rats which were divided into 4 treatment groups with 3 replications. K0 consisted of ovariectomized rats without Cissus quadrangularis Salisb exstract, wheares K1, K2 and K3 consisted of ovariectomized rats  and were given Sipatah-patah extract with 500mg/kg body weight, 700/mg/kg body weight and 900mg/kg body weight for 30 days. On 31st day, rats were euthanized with cloroform and mandible bones were collected for histological preparation. Parameters observed were bone structures (osteosit, osteoblast, osteoclast and trabekula). The results showed that in K0 group, bone density was decreased and became thinner, osteoclast cells were found on trabekula, and low density of active and passive osteoblast were also detected. The treatment group (K1 and K2) showed an improvement stucture of trabekula,where the amount of osteoclast were lower than K0, as well as the amount of active osteoblast, although a lot of passive osteoblast were still found. The treatment group (K3) showed an improvement as the most dense trabekula structure with large amount of active osteoblast cell density without the existance of osteoclast compared to other grups. In this research, it would be concluded that the adding sipatah-patah extract with a dose of 900 mg/kb body weight showed a higher number of active osteoblasts and trabekula density compared to the control groups, K1, and K2 on ovariectomized mandible bone rats